Effects of the Application of Information Technology to E-Book Learning on Learning Motivation and Effectiveness - Sun, Li; Pan, Cheng En (Frontiers in Psychology, 2021)
Along with the rapid development of electronic technology, the appeal of information technology to students and teachers in domestic and international information education has become universal. Education-related departments aim to positively cultivate teachers’ professional information knowledge and skills. The use of information technology in instruction allows students to enhance their creativity and learning motivation. A total of 306 college students from Fujian Province participated in the experimental research. The results show that (1) The application of information technology to e-book teaching could enhance students’ sense of achievement in self-directed learning. Students could answer test questions in a confidential and relaxed manner. (2) The application of information technology to e-book teaching activates teaching flexibility. Many teaching models, such as teaching by wandering around, interactive teaching, and blended teaching, are therefore derived to enhance the richness of teaching. (3) The application of information technology to e-book teaching bridges the distance between instructors and students and leads to a deeper understanding of students’ learning conditions, expanding the possibilities for content planning and teaching models. The results give rise to suggestions enhancing enjoyment in learning and promoting higher motivation and more effective teaching.